P490 Etrasimod for the treatment of ulcerative colitis: up to 2.5 years of pooled safety data from global clinical trials. (30th January 2023) - Vermeire, S; Peyrin-Biroulet, L; Panés, J; Regueiro, M; Kotze, P G; Charabaty, A; Goetsch, M; Shan, K; Wu, J; McDonnell, A; Woolcott, J; Danese, S
Abstract: Background: Etrasimod is an investigational, once-daily, oral, selective sphingosine 1-phosphate receptor 1, 4, 5 (S1P1, 4, 5 ) modulator in development for the treatment of moderately to severely active ulcerative colitis (UC). The safety and efficacy of etrasimod for the treatment of moderate to severe UC has been evaluated in the OASIS phase 2 and ELEVATE phase 3 placebo (PBO)-controlled trials. Long-term safety and efficacy of etrasimod for UC are being evaluated in an ongoing, open-label extension (OLE) study. We report an integrated analysis of the cumulative safety profile observed during the clinical development programme. Methods: Safety outcomes included adverse event (AE) frequency and exposure-adjusted incidence rates (EAIRs) of AEs of interest determined based on safety data from PBO-controlled trials and OLE trials. Patients who received PBO or etrasimod (1 or 2 mg) were analysed as two cohorts: patients who received either PBO or etrasimod as part of one phase 2 study (etrasimod 1 or 2 mg for 12 weeks; NCT02447302) or two phase 3 studies (etrasimod 2 mg for 12 or 52 weeks; NCT03945188 and NCT03996369) were reported as the PBO-controlled cohort, and all patients who received ≥1 dose of etrasimod in the all UC cohort (studies above, NCT02536404, NCT03950232, and open-label period of NCT04176588; data cut-off January 31, 2022). Patients may have participated in >1 study. Results: Overall, 956 patients received ≥1 dose of etrasimod with 769.3 patient years (PY) of exposure with demographics for both cohorts reported in Table 1. In the PBO-controlled cohort, a total of 629 and 314 patients received etrasimod and PBO, respectively, with 288.1 and 115.1 PY of exposure. Mean (SD) exposure per patient was 23.9 (18.5) and 19.1 (15.1) weeks for etrasimod and PBO, respectively. Of the 956 patients who received etrasimod in the all UC cohort, mean (SD) exposure was 42.0 (27.5) weeks. Rates for AEs, serious AEs, and infections (including serious infections, opportunistic infections, and herpes zoster) were similar between treatment arms and between the PBO-controlled and all UC cohorts (Table 2). Eleven (1.8%) etrasimod-treated patients reported events of bradycardia (EAIR=0.04) in the PBO-controlled cohort (9 of 11 events were asymptomatic); no events were reported in PBO-treated patients. Other AEs of special interest including hypertension and macular oedema were similar between treatment arms and with the all UC cohort. Conclusion: Etrasimod in patients with moderately to severely active UC was overall well tolerated and had an acceptable safety profile that did not appear to change with longer-term treatment of up to 2.5 years. In the PBO-controlled cohort, serious infections and herpes zoster were more commonly reported among PBO patients.